Rewriting the Script of Elder Care: Human-Centered Perspectives on the Shift from Charity to Rights-Based Approaches - Kripanjali Tellis Nayak; Dr Kavyashree. K (Educational Administration: Theory and Practice, 2024)
The aging population in India presents unique challenges and opportunities for transforming elder care. Historically, elder care has been viewed through a charity-based lens, where elderly individuals are considered dependent and passive recipients of care. However, the evolving discourse around aging is now emphasizing a rights-based approach, where older adults are recognized as active agents with inherent rights to autonomy, dignity, and participation in decision-making regarding their care. This paper examines the shift from a charity-driven model to a human-centered, rights-based framework in Indian aged care institutions. Using a case study of an aged care home in Mangalore, this research explores how gender dynamics influence the delivery and experience of care, with a focus on elderly women’s changing roles and the impact of this transformation on their autonomy. Through qualitative analysis, including interviews with caregivers, administrators, and residents, the study identifies critical factors facilitating or hindering the successful implementation of rights-based care. Findings suggest that while there is growing recognition of elderly individuals’ rights, cultural, economic, and systemic barriers persist, particularly for vulnerable groups. The paper argues that human-centered approaches into policy and practice are essential for achieving sustainable, equitable elder care in India. This work contributes to the broader field of gerontology, offering insights into how shifting paradigms can reshape the landscape of aging and care provision in developing countries.